Typification of two names in the genus Ranunculus (Ranunculaceae) - Ferrer-Gallego, P. Pablo; Sáez, Llorenç (Phytotaxa, 2022)
The typification of the names Ranunculus chaerophyllos var. balearicus and R. weyleri is discussed. These two names are lectotypified using specimens preserved at COI.